Incidence, associated factors, and outcomes of delirium in critically ill children in china: a prospective cohort study - Lei Lei; Yi Li; Huilin Xu; Qin Zhang; Jiacai Wu; Shoujv Zhao; Xiaochao Zhang; Min Xu; Shuai Zhang (BMC Psychiatry, 2023)
Abstract Background Delirium occurs frequently in critically ill children and has been reported in many countries, but delirium is not well-characterized in China. The aim of this study was to represent the incidence of delirium in critically ill children in China, its associated factors, and the influence of delirium on in-hospital outcomes. Methods This observational prospective cohort study was set up in a large academic medical center with a 57-bed PICU in southwestern China. Critically ill children who required PICU stays over 24 h and were admitted between November 2019 and February 2022 were included in this study. The Cornell Assessment of Pediatric Delirium was used twice daily for delirium evaluation by bedside nurses, and twenty-four clinical features were collected from medical and nursing records during hospitalization. Results The incidence of delirium was 26.0% (n = 410/1576). Multivariate analysis revealed that seven independent risk factors including days of mechanical ventilation and physical restraints, admission diagnosis (neurologic disorder), sleep deprivation, use of benzodiazepines and dexmedetomidine, liver failure/liver dysfunction associated with delirium in critically ill children. One potentially protective factor was the watching television /listening to music/playing with toys. Children with delirium had longer lengths of stay in the PICU (median 11 vs. 10 days, p < 0.001) and hospital (median 18 vs. 15 days, p < 0.001) compared to those without delirium. Additionally, the in-hospital mortality rates were 4.63% and 0.77% in patients with and without delirium (p < 0.05). Conclusions Delirium is common in critically ill children in China and related to poor outcomes. Interventional studies are warranted to determine the best practices to reduce delirium exposure in at-risk children.